1978
DOI: 10.1111/j.1471-0307.1978.tb01384.x
|View full text |Cite
|
Sign up to set email alerts
|

Rearing Dairy Herd Replacements

Abstract: A reduction in the age of calving of heifers should give a quicker return on capital; reduce the number of dairy heifer replacements being reared at any one time; and allow the assessment of the genetic value of a heifer at a younger age. Target weights for first calving at different ages are suggested. The desired age of first calving may not be achieved because of late puberty. Age at puberty is affected both by growth rate and season of birth. The greatest deterrent to a reduced age at calving is the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Most of the research involved overconditioning or liberal feeding of heifers; however, some work suggested that heifers raised on low or medium nutrition produced slightly more milk than heifers raised on high nutrition. Since then objectives of several studies (8,62,68,74) have concerned a rate of development that allows for calving at 24 mo, efficient use of feed during rearing, delivery of a healthy, vigorous calf, few calving problems, production at maximum genetic potential in first lactation, resistance to metabolic problems and infections, enough size successfully to compete for feed, and longevity.…”
Section: Rearing Rates Of Heifersmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the research involved overconditioning or liberal feeding of heifers; however, some work suggested that heifers raised on low or medium nutrition produced slightly more milk than heifers raised on high nutrition. Since then objectives of several studies (8,62,68,74) have concerned a rate of development that allows for calving at 24 mo, efficient use of feed during rearing, delivery of a healthy, vigorous calf, few calving problems, production at maximum genetic potential in first lactation, resistance to metabolic problems and infections, enough size successfully to compete for feed, and longevity.…”
Section: Rearing Rates Of Heifersmentioning
confidence: 99%
“…First estrus occurs earlier and at lower weights for small breeds than for large breeds. If heifers are fed to gain .9 to 1.0 kg/day, first estrus may be as early as 6 to 8 mo for Holsteins (62). Swanson (73)has predicted puberty at 10 mo with .82 kg gain/day, 11 mo with .68 kg gain/day, and 14 mo with .54 kg gain/day.…”
Section: Rearing Rates Of Heifersmentioning
confidence: 99%
“…Only 005 of heifers had condition scores outside this range, and only 001 of heifers were both infertile and in an extreme body condition category. The evidence reviewed by Roy (1978) also indicates that heifers need to be growing at rates of approximately 0-7 kg/day if they are to attain live weights necessary for satisfactory reproduction and subsequent performance. Mulvany (1977) found that, for dairy cows inseminated in early lactation, there was an association between body condition score and pregnancy rate.…”
Section: Discussionmentioning
confidence: 99%
“…Kilkenny and Herbert (1976) and Roy (1978) concluded that heifers need to grow at an average rate of at least 0-6 kg/day if they are to attain the necessary live weight at service and pre-calving necessary for satisfactory fertility and subsequent milk production. Kilkenny and Herbert (1976) and Roy (1978) concluded that heifers need to grow at an average rate of at least 0-6 kg/day if they are to attain the necessary live weight at service and pre-calving necessary for satisfactory fertility and subsequent milk production.…”
Section: Introductionmentioning
confidence: 99%
“…A greater availability of heifers also enables dairy producers to aggressively cull poor-performing heifers, as well as those with lower genetic merit (Roy 2007).…”
Section: Introductionmentioning
confidence: 99%